Cervical cyst of the ligamentum flavum and C7-T1 subluxation: case report - Gazzeri, Roberto (Springer-Verlag, 2005)
A patient with progressive gait disturbance resulting from a cyst of the cervical ligamentum flavum associated with C7-T1 listhesis is reported. Surgical removal of the cyst improved the patient’s myelopathy. Intraspinal degenerative cysts are preferentially located in the lumbar region:unusual is the cervical localization. Differential diagnosis includes ligamentum flavum cyst, synovial and ganglion cysts. Association between degenerative intraspinal cysts and listhesis is discussed. To our knowledge, this is the first case of cyst of the ligamentum flavum associated with cervical subluxation.